Utilization of Turmeric Media to Improve Motor Ability to Write Hijaiyah Letters - Irmawati (Proceeding International Conference on Religion, Science and Education, 2022)
The background of this research is the low motoric ability of children in writing hijaiyah letters and learning seems boring because they only use the same media every day. This study aims to improve children’s motor skills in writing hijaiyah letters through the use of turmeric media. This research is a Classroom Action Research conducted in class B TK Pertiwi 26-13 Bogares Kidul, using 20 children as research subjects. The instrument uses observation notes, interviews and documentation. The results showed that children’s hijaiyah writing motor skills could be improved by using turmeric media. The results of the first cycle showed that there was an increase in motor skills in writing hijaiyah letters compared to before the action. In the second cycle, the percentage obtained is greater and is in the Very Good Developing criteria, which has reached the predetermined success indicators. Thus, it can be said that the motor skills of children in writing hijaiyah letters for grade B children in Kindergarten Pertiwi 26-13 Bogares Kidul can be increased by using turmeric media.